2003
DOI: 10.2176/nmc.43.329
|View full text |Cite
|
Sign up to set email alerts
|

Branches of the Anterior Cerebral Artery Near the Anterior Communicating Artery Complex: an Anatomic Study and Surgical Perspective

Abstract: The anatomy of the branches of the anterior cerebral artery (ACA) near the anterior communicating artery (ACoA) complex were investigated to minimize neurovascular morbidity caused by surgical procedures performed in this region. Thirty-one cadaver brains were perfused with colored silicone, fixed, and studied under the operating microscope. The recurrent artery of Heubner (RAH), orbitofrontal artery (OFA), and frontopolar artery (FPA) were identified as the branches of the ACA arising near the ACoA complex. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 8 publications
7
47
0
4
Order By: Relevance
“…10 The largest perforating branch of the ACAs is the RAH. The recent anatomic study of Avci et al 11 on 62 hemispheres showed that the RAH was unilateral in 75% of cases and most often arose from the communicating segment (28.5%) or the A2 segment (63.6%) and rarely from the A1 segment (7.8%). The RAH vascularizes the anterior limb of the internal capsule, the head of caudate nucleus, and the anterior lentiform nucleus.…”
Section: Ischemia Related To A1 Occlusionmentioning
confidence: 98%
“…10 The largest perforating branch of the ACAs is the RAH. The recent anatomic study of Avci et al 11 on 62 hemispheres showed that the RAH was unilateral in 75% of cases and most often arose from the communicating segment (28.5%) or the A2 segment (63.6%) and rarely from the A1 segment (7.8%). The RAH vascularizes the anterior limb of the internal capsule, the head of caudate nucleus, and the anterior lentiform nucleus.…”
Section: Ischemia Related To A1 Occlusionmentioning
confidence: 98%
“…Although the neurosurgical anatomy of the ACAs has been well described, most diagnostic brain procedures and techniques have used morphometric data regarding the diameter and length of the A2 segment based on measurements derived from cadaveric studies (Alpers et al, 1959;Avci et al, 2003;Baptista, 1963;Kawashima et al, 2005;Kwolek-Klimkiewicz et al, 1996;Pai et al, 2005;Rhoton, 1976, 1978;Stefani et al, 2000). However, cadaveric studies have some morphometric limitations such as the measurement of the external diameter of the vessel, without taking into account the vessel curvature and geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre esses ramos, a artéria frontobasilar medial (AFM), também chamada na língua inglesa de medial orbitofrontal artery, é a que possui o percurso cortical mais próximo da BAC (Rhoton, 2002;Avci et al, 2003) tornando-se potencialmente o primeiro grande vaso a ser lesionado, se houver trauma da BAC durante uma cirurgia endonasal (Figura 1). Dependendo da doença e da suspeita de estruturas vasculares ou neurais envolvidas em lesões da base do crânio, o estudo pré-operatório deve incluir uma ressonância magnética com gadolínio do cérebro, base do crânio e dos seios paranasais ou uma angiotomografia computadorizada (Field et al, 2010).…”
Section: Discussionunclassified
“…Isto ocorre no estudo da AFM, que pode ser dissecada por craniotomia como nos estudos de Mavridis et al, (2016) e Avci et al, (2003). Nestes casos houve tração ou remoção do cérebro da caixa craniana, o que modifica a posição inicial da AFM e não permite o estudo das suas relações com estruturas nasais.…”
Section: Discussionunclassified
See 1 more Smart Citation